Standard Contract in Financing at Sharia' Bank - Trisadini Prasastinah Usanti; Ari Kurniawan (Rechtsidee, 2017)
Standard contract is a contract which is merely made by one of the parties and other parties agree to a contract. In practice Indonesia sharia bank, all financing contracts are made by Islamic bank in the form of Islamic standard contract. As a result, there is no negotiation between the parties. Therefore, this research will analyze standard contract in financing at sharia bank X and sharia bank Y in Indonesia. This research employs statute approach, conceptual approach and contractual approach. The outcome of this research is Islamic standard contract of financing at Sharia’ Bank are not contrary to Islamic principles throughout the contract meets the validity of contract, there is no element of which is prohibited according to the Shariah, namely gharar, maysir, usury and does not violate the principles of sharia agreement. Islamic standard contract at sharia bank X and sharia bank Y in Indonesia had described the characteristic of each Islamic financing and has met the minimum requirements accordance with the fatwa of Sharia’ supervisory board (DSN-MUI) which is regulated by the regulations of Bank Indonesia.